Advances, hotspots, and trends in restorative environment research over the past 30 years: a bibliometric analysis based on the WoS database - Yang, Zihan; Tu, Zhigang; Huang, Zhongshan (Frontiers in Environmental Science, 2025)
In the face of mounting pressures in modern society, research into restorative environments has emerged as a crucial field addressing issues related to mental health and environmental wellbeing. This study presents a comprehensive bibliometric analysis of 919 publications on restorative environment research, spanning from 1993 to 2024, utilizing VOSviewer and CiteSpace for data visualization, based on the Web of Science database. The main objective of this bibliometric analysis is to provide scholars and researchers with a deeper insight into the current state and evolving trends in restorative environment research, while also pinpointing areas that warrant further investigation. The study examines research patterns across several key dimensions, including publication volume, keywords, journals, academic disciplines, countries, institutions, and individual researchers. The results of this analysis highlight the following key points: (1) Research on restorative environments has experienced significant growth since 2014, with a marked acceleration during the COVID-19 pandemic. (2) The primary research foci include environmental psychology, the relationship between nature and social wellbeing, and urban ecosystems with aesthetic health, with environmental psychology and cognitive restoration emerging as the most interconnected core themes. (3) Leading journals in restorative environment research include the Journal of Environmental Psychology, the International Journal of Environmental Research and Public Health, and Frontiers in Psychology. (4) The main academic fields contributing to this body of research are psychology, public health, landscape architecture, and urban planning. (5) The United States has the highest number of publications on restorative environments (212 papers), followed by China (159 papers), the United Kingdom (90 papers), Sweden (67 papers), and Australia (55 papers). (6) Uppsala University has emerged as the most prolific institution, with 35 publications, followed by the Swedish University of Agricultural Sciences (32 papers) and the University of Exeter (24 papers). Finally, environmental psychology and cognitive restoration, the connection between nature and social wellbeing, and urban ecosystems with aesthetic health are identified as the leading and most dynamic research areas. These findings suggest that restorative environment research has made significant strides over the past 3 decades and is poised to continue expanding in the years ahead.